The Importance of Changing Management Styles in The Digital Age - Budi Hartono; Maksum, Ikhsan (Journal of Industrial Engineering & Management Research, 2020)
Digital technology has required organizations to be more flexible. The technological changes that occur seem to exceed the speed of the organization in preparing human resources to adapt to the latest technology. Digitalization shapes organizations, work environments, and processes into new challenge zones that leaders must-have. Many organizational researchers and social science experts have tried to understand this phenomenon, but the findings are well-known in the scientific discipline do not come together in a clear picture. This study aims to add to the literature on leadership and digitization. The method used is library research to provide an analysis of leadership studies and digitization by identifying patterns of thought from previous findings. The findings in this study indicate that leaders are key figures in organizations who are ready to move toward organizations that are flexible and adaptive to digital change. Leaders need to create relationships with stakeholders and focus on collaborative efforts. With this research, it is hoped that we can contribute to advancing theoretical studies on digital transformation and digital leadership (e-digital). Limitations of this study are the absence of empirical findings to expand understanding and create a more systematic research model framework. Future research opportunities are still wide open to advance knowledge in this field.